WEWENANG PENGGUNAAN KEKUATAN TINDAKAN KEPOLISIAN DALAM MENJALANKAN TUGAS YANG MENGAKIBATKAN PELANGGARAN HAK ASASI MANUSIA - Surnawan, Eko Idya; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2024)
This research examines the authority to use force of action by the police in carrying out tasks that result in violations of human rights. The purpose of this study is to analyze how the regulations related to the use of force in police action and whether members of the police when carrying out tasks that result in violations of human rights can be punished. This research method uses normative legal research. The results of this study explain that in broad terms the arrangements regarding the authority to use force in police action have been regulated separately in the Regulation of the Head of the Indonesian National Police Number 1 of 2009 concerning the Use of Force in Police Action, which in this regulation has explained in depth how the powers of members of the police using acts of force in carrying out their duties in the midst of society, these rules have also emphasized that police actions are forced efforts or other actions that are carried out responsibly according to law And members of the police when carrying out tasks that violate human rights can be held accountable according to what what they do, law enforcement must always be upheld as fairly as possible because whoever does it is he who must be held responsible, in one of the articles, the rule also explains that the form of liability the response of members of the police who have committed violations of human rights must be held accountable for their actions according to what they have done, human rights must always be defended or protected by the State.